2004
DOI: 10.1182/blood-2003-09-3074
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of somatic mutations in the AML1/RUNX1 gene in myelodysplastic syndrome and low blast percentage myeloid leukemia with myelodysplasia

Abstract: A high incidence of somatically acquired point mutations in the AML1/RUNX1 gene has been reported in poorly differentiated acute myeloid leukemia (AML, M0) and in radiation-associated and therapy-related myelodysplastic syndrome (MDS) or AML. The vast majority of AML1 mutations identified in these diseases were localized in the amino (N)-terminal region, especially in the DNA-binding Runt homology domain. In this report, we show that AML1 point mutations were found in 26 (23.6%) of 110 patients with refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
248
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(266 citation statements)
references
References 31 publications
15
248
0
2
Order By: Relevance
“…19 We found BM mononuclear cells from MDS/AML patients harboring RUNX1-C-terminal mutations had significantly lower GAD-D45A expression compared with those from MDS/AML patients with WT RUNX1 (P ¼ 0.0233; Figure 6). …”
Section: Runx1 Transcriptionally Regulates Gadd45a Expressionmentioning
confidence: 92%
See 1 more Smart Citation
“…19 We found BM mononuclear cells from MDS/AML patients harboring RUNX1-C-terminal mutations had significantly lower GAD-D45A expression compared with those from MDS/AML patients with WT RUNX1 (P ¼ 0.0233; Figure 6). …”
Section: Runx1 Transcriptionally Regulates Gadd45a Expressionmentioning
confidence: 92%
“…19,38,39 We speculate that a RUNX1 mutation may be a cause of additional mutation(s) through the impaired DDR response. In future studies, whole genome analysis of MDS/AML samples harboring RUNX1 mutations would clarify the role of RUNX1 mutations in the occurrence of genetic abnormalities in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…C-terminal mutations are seen at lower frequency and almost exclusively in MDS or AML following MDS, and seem to be associated with poor prognosis. 132 A high frequency (40%) of N-terminal AML1 mutation has also been observed in t-AML and t-MDS. 132 Some monoallelic mutations may act in a dominant-negative manner through inhibition of the effects the remaining WT AML1.…”
Section: Aml1mentioning
confidence: 99%
“…132 A high frequency (40%) of N-terminal AML1 mutation has also been observed in t-AML and t-MDS. 132 Some monoallelic mutations may act in a dominant-negative manner through inhibition of the effects the remaining WT AML1. This hypothesis was confirmed by Osato et al and Imai et al, 124,126 who demonstrated that some AML1 gene missense mutation cotransfected with WT AML1 abolished transactivation of the M-CSF receptor promoter.…”
Section: Aml1mentioning
confidence: 99%
“…Indeed, RUNX1 mutations have frequently been identified in patients with MDS and AML [6,7]. Furthermore, a higher frequency of RUNX1 mutations (30-50%) has been reported in therapyrelated and radiation-associated MDS and AML [13][14][15]. In general, RUNX1 mutations are considered to result in the loss of RUNX1 functions.…”
Section: Abstract Runx1 · Fpd/aml · Fpd/mm · Germ Line Mutationmentioning
confidence: 99%